2019
DOI: 10.1111/and.13238
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol reduces quality parameters and increases DNA damage in mice spermatozoa

Abstract: This study was performed to investigate in vitro effects of deoxynivalenol (DON) on mice sperm quality parameters including viability, motility and DNA damages at various concentrations and exposure times. Mice spermatozoa were exposed to DON at 0, 2.5, 5 and 10 µM for 1, 3 and 6 hr, motility parameters were evaluated by computer‐assisted analysis and viability was examined by colorimetric metabolic activity assay and HOS test. DNA damage was examined by acridine orange staining, and sperm damages via lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…However, studies on the effects of DON on semen of other species have showed interesting results. In a recent study on mice sperm, Salahipour and coworkers observed a dose-dependent toxic effect of 2.5–10 μM DON with a reduction in sperm metabolic activity and membrane integrity, and an increase in lipid peroxidation rate and DNA damage [ 44 ]. By contrast, in our study, toxic effects of DON on boar semen were not observed at concentrations up to 50.6 μM, and we did not detect an effect on DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the effects of DON on semen of other species have showed interesting results. In a recent study on mice sperm, Salahipour and coworkers observed a dose-dependent toxic effect of 2.5–10 μM DON with a reduction in sperm metabolic activity and membrane integrity, and an increase in lipid peroxidation rate and DNA damage [ 44 ]. By contrast, in our study, toxic effects of DON on boar semen were not observed at concentrations up to 50.6 μM, and we did not detect an effect on DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many studies have shown that DON can cause excessive ROS and induce DNA damage. For example, after 6 h of exposure to 10 µM DON, DNA damage in mouse sperm was significantly increased, accompanied by a 2.5-fold increase in MDA content [ 12 , 13 ]. However, it is not clear whether low dose sub-chronic DON exposure influences the liver’s antioxidant enzyme activities, DNA damage, and DNA repair ability.…”
Section: Introductionmentioning
confidence: 99%
“…DON was revealed to inhibit cell proliferation in different conditions (32,33). In the present study, the allicin both inhibited cell proliferation and aggravated the DON-induced barrier damages within the experimental condition, which may be attributed to the synergy-effects of DON and allicin in restraining DNA formation (34,35). Contrary to the roles of allicin in the DON-induced damage model, allicin successfully prevented the LPS-induced damages to intestinal barrier function, which prompts us to further validate its effects and explore potential mechanisms.…”
Section: Discussionmentioning
confidence: 48%